Heterozygous Single Nucleotide Polymorphic Loci in Haploid Gametophytes of Gracilariopsis lemaneiformis (Rhodophyta) - Hu, Yiyi; Sui, Zhenghong; Zhou, Wei; Wang, Jinguo; Jiang, Minjie; Chen, Haihong; Zhang, Jingyu; Zhang, Wei; Feng, Xiaoqing; Lei, Yuehua; Xiao, Baoheng; Guo, Peng (Frontiers in Genetics, 2019)
Gracilariopsis lemaneiformis is an important commercial macroalga. Whole-genome resequencing was conducted to identify single nucleotide polymorphisms (SNPs) in parental gametophytes and 60 F1 gametophytes of Gp. lemaneiformis in this study, and 9,989 SNPs located in nonrepetitive sequences were obtained. Among these SNPs, 92.02% of loci were identified as having a heterozygous genotype in at least one gametophyte, and 48.07% of loci had identical heterozygous genotypes in the 62 gametophytes. For each gametophyte, the proportions of homozygous and heterozygous loci ranged between 13.74% and 21.61% (mean of 17.04%) and between 66.36% and 83.59% (mean of 77.12%), respectively. The remainder were missing loci, representing an average 5.84%. Sources of heterozygous SNPs were free of exogenous DNA contamination, cross contamination among individuals, plastid and mitochondrial sequences, chimeras of different thallus parts or different cells, and repetitive sequences. Genotypes of heterozygous SNPs were verified by Sanger sequencing of PCR products and monoclones. Duplications of chromosomal rearrangements in the genome of Gp. lemaneiformis might explain the presence of heterozygous SNPs in haploid gametophytes.